Common Tropical Illness Due to Uncommon Species - Madhuri Kadam (Pediatric Infectious Disease)
Aim and background: This case report details a rare instance of Salmonella Gallinarum infection in a human with a history of exposure to poultry. Case description: A 12-year-old boy presented with fever, respiratory symptoms, and leukopenia, diagnosed with Salmonella Gallinarum, likely contracted from contact with poultry. Ceftriaxone and azithromycin were effective, leading to clinical improvement. Family members, especially the child caring for animals, received education on hand hygiene and improved animal care practices to prevent future zoonotic exposures. Follow-up blood cultures confirmed Salmonella Gallinarum clearance. Conclusion: The case underscores the importance of considering zoonotic sources in febrile illnesses and highlights the role of comprehensive hygiene measures in preventing such infections, especially in households with diverse animal exposure. Clinical significance: Salmonella Gallinarum infections in humans are rare, and the symptoms are generally consistent with those of salmonellosis caused by other Salmonella serotypes. The infection typically occurs due to close contact with infected birds, particularly poultry.